AZANGÍ GIMNASTIKALÍQ SHÍNÍǴÍWLAR MENEN SHUǴÍLLANÍWDÍŃ INSAN SALAMATLÍǴÍNA TÁSIRI - Ramazanov, M.; Joldasbaev, P. (SCIENCE and SOCIETY, 2019)
The article is devoted to the importance of physical exercises for the health of a person, to the study of method for strengthening the health with the help of morning exercises, that are recommended to do regularly.